Неформальна освіта як важлива складова системи освіти дорослих - Терьохіна, Наталя (Studies in Comparative Education, 2014)
Стаття присвячена проблемам розвитку неформальної освіти як важливої складової системи освіти дорослих. У статті подано визначення неформальної, формальної та інформальної (спонтанної) освіти. Визначено ознаки та завдання неформальної освіти; виділено загальні характеристики неформального навчання. Наголошено на ролі та значенні неформальної освіти дорослих як основоположного поняття освіти впродовж життя; підкреслено важливість надання якісних освітніх послуг у сфері неформальної освіти дорослих, проаналізовано навчальні програми у галузі неформальної освіти дорослих, а також охарактеризовано їх змістове наповнення; підкреслено важливість неформальної освіти в контексті освіти в рамках Університету третього віку. Статья посвящена проблемам развития неформального образования как важной составляющей системы образования взрослых. В статье дается определение неформального, формального и информального (спонтанного) образования. Определены признаки и задачи неформального образования; выделены общие характеристики неформального обучения. Отмечена роль и значение неформального образования взрослых как основополагающего понятия образования в течение жизни; подчеркнута важность предоставления качественных образовательных услуг в сфере неформального образования взрослых, проанализированы учебные программы в области неформального образования взрослых; подчеркнута важность неформального образования в контексте образования в рамках Университета третьего возраста. This article is devoted to the problems of non-formal education as an important component for adult education. Non-formal, formal and informal (spontaneous) education are explained in the article. Main features and tasks of non-formal education are defined; common characteristics of non-formal learning are identified. The role and importance of non-formal adult education as a fundamental concept of continuing education is underlined; the importance of providing qualitative educational services in the field of non-formal adult education is stressed; the importance of non-formal education in the context of education in the University of the Third Age is emphasized. Non-formal education is described as a pedagogical modal for adult education, which contains a great potential for continuing education. Most highly-developed countries reform their education systems on the principles of the concept of lifelong learning. UNESCO introduced the special terms which reflect different educational services: formal, non-formal, informal education. Formal education can not fully meet the educational needs of the citizens. Non-formal education has a great potential due to the fact that this form is able to more flexible respond to new needs and offer educational system and the labor market what is needed in terms of time, content and organization of learning. Non-formal education takes place in any place (school, society, church, family, etc.); in the individual or group form; at any age, which once again confirms the existence of non-formal education as a part of lifelong learning. The source of non-formal education can be museums, schools, institutes, television, newspapers, own experience. Programs for non-formal education are organized in a way to be as friendly for a customer as possible. UNESCO and the Council of Europe promote recognition of non-formal learning. Non-formal education is an important component of lifelong adult education; it has been developing as a result of social development and nowadays it is in great demand. Non-formal education has great potential for the development of society, the state, the individual.